1-1-06. Repeated, cortical stimulation can modify the wideband cortical activity correlates of interictal epileptiform discharge. Issue 6 (June 2017) - Nakatani, Mitsuyoshi; Matsumoto, Riki; Kobayashi, Katsuya; Hitomi, Takefumi; Inouchi, Morito; Matsuhashi, Masao; Kinoshita, Masako; Takayuki
Abstract : Electric cortical stimulation (ECS) is known to have suppressive effects on epileptic focus. However, the inhibitory mechanism remains to be elucidated. We investigated the effect of ECS on human epileptic focus by evaluating wideband cortical activities accompanied with interictal epileptiform discharges (IEDs). We recruited 9 patients with intractable partial epilepsy who underwent invasive pre-surgical evaluation with subdural electrodes. 50-Hz stimulation (0.3 ms pulse, 1–15 mA, 1–5 s) was applied at seizure onset zone (SOZ) as a part of functional cortical mapping. By performing Hilbert transform, we calculated the power of 4 frequency bands: fast ripple (200–300 Hz), ripple (80–200 Hz), low gamma (30–50 Hz) and beta (15–30 Hz). We compared them between pre- and post ECS at the timing of spike peak of IEDs. 2 patients were excluded due to artifacts or no examinations. In 3 patients, the power decreased after ECS in all frequency bands. The power did not change in 1, and the power change varied depending on the frequency band or the time after ECS in 3. We demonstrated that 50-Hz ECS on epileptic focus can suppress wide-band activities accompanied with IEDs, suggesting its potential ability to modulate cortical excitability toward less excitation and more inhibition.